Internal marketing management and its relationship to attracting administrative competencies in local banks in the State of Kuwait - Ashkanani, Safia Mukhtar; Al-Mashaan, Aisha Meshaal (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aims to shed light on the management of internal marketing and its relationship in strengthening the attraction of administrative competencies in local banks in the State of Kuwait, and in order to achieve the objectives of the study, the correlational descriptive approach was used, and the study sample was selected in an accessible manner consisting of (110) employees of local banks, and its questionnaire was used as a tool for the study, and honesty and stability were verified through the method of internal consistency according to the Cronbach alpha equation and after collecting and analyzing the data statistically, many results were reached The most important was that there is a strong relationship between internal marketing management and attracting administrative competencies in local banks in the State of Kuwait, and it was found that the degree of internal marketing management in local banks in the State of Kuwait from the point of view of employees is large, and that the degree of attracting administrative competencies in local banks in the State of Kuwait from the point of view of employees is also large, and the study came out after recommendations, the most important of which was that the bank’s management should continue to have a communication system that allows the delivery of information to employees. To perform their duties, the bank’s management must continue to strive to put the right person in the right place.